ON THE ESTIMATION OF THE LIFETIME OF THE ACCRETION DISK IN THE SEMIDETACHED BINARIES - Kilpio, A. A. (Одеські астрономічні публікації, 2017)
The results of 3D numerical simulations of mass transfer in semidetached binaries after the mass transfer termination are presented. On the first stage the 3D gasdynamical simulation of mass transfer for the case of constant rate of mass transfer has been conducted up to the steady-state solution. Then the matter out was adopted to be terminated and the dependency of the lifetime of residual disk on numerical viscosity has been considered.